Spike-specific IgG4 generated post BNT162b2 mRNA vaccination is inhibitory when directly competing with functional IgG subclasses - Jerry C.H. Tam; Abbie C. Sibayan; Jeffrey Seow; Carl Graham; Ashwini Kurshan; Blair Merrick; Richard J. Stanton; Katie J. Doores (Cell Reports)
Summary: COVID-19 vaccines proved vital in controlling the SARS-CoV-2 pandemic. Both neutralizing and effector-function activities of Spike-specific antibodies are important for their protective activity. Several studies have reported that COVID-19 mRNA vaccines can lead to elevated levels of Spike-specific immunoglobulin G4 (IgG4), an anti-inflammatory subclass with reduced binding to Fcγ receptors. We show that Spike-specific IgG4 levels following BNT162b2 vaccination are impacted by the interval between and frequency of vaccine boosts, prior or post SARS-CoV-2 infection and bivalent vaccine boosters. Through expression of IgG1, IgG2, IgG3, and IgG4 subclasses of SARS-CoV-2 antibodies, we demonstrate that while IgG4 has reduced effector-function activity, including antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent complement deposition (ADCD), and antibody-dependent cellular phagocytosis, IgG4 is only inhibitory when directly competing with functional IgG subclasses binding to overlapping epitopes. ADCC and ADCD activity in plasma was not depleted by adding a cocktail of Spike-specific IgG4 monoclonal antibodies, suggesting that the non-stimulatory effect of Spike-specific IgG4 may be hidden in polyclonal mixes.